1992
DOI: 10.1093/jac/30.6.803
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofilm culture upon the susceptibility of Staphylococcus epidermidis to tobramycin

Abstract: Biofilms of Staphylococcus epidermidis were cultured at various specific growth rates, and susceptibilities to tobramycin were compared with those of equivalent plank-tonic populations. In all instances, susceptibility increased significantly with increasing specific growth rate. However, resuspension of the biofilms increased susceptibility, suggesting some involvement of the glycocalyx in reducing antibiotic permeation of the biofilm. Cells that dispersed spontaneously from the biofilms at steady state were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 0 publications
3
50
0
1
Order By: Relevance
“…If slow penetration is the sole basis for biofilm tolerance, we would anticipate that dispersal of a biofilm would immediately and completely restore its full planktonic susceptibility. This behavior has been reported in some studies (2,16,42,45).…”
Section: Resultssupporting
confidence: 82%
“…If slow penetration is the sole basis for biofilm tolerance, we would anticipate that dispersal of a biofilm would immediately and completely restore its full planktonic susceptibility. This behavior has been reported in some studies (2,16,42,45).…”
Section: Resultssupporting
confidence: 82%
“…Hoyle et al (83) found that dispersed bacterial cells were 15 times more susceptible to tobramycin than were cells in intact biofilms. DuGuid et al (57) examined Staphylococcus epidermidis susceptibility to tobramycin and concluded that the organization of cells within biofilms could in part explain the resistance of this organism to this antimicrobial agent.…”
Section: Delayed Penetration Of the Antimicrobial Agentmentioning
confidence: 99%
“…However, these observations do not permit us to determine which metabolic activity in CoNS should be considered normal or a reference metabolic state. As mentioned above, there is a large amount of experimental evidence that indicates that metabolically less active bacteria have reduced susceptibility to many antibiotics (3,4,(9)(10)(11). Consequently, the observed decreased metabolic activity during late FBI can explain at least in part why these infections are so difficult to eradicate with conventional antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The exact nature of the resistance remains unclear, but decreased metabolic activity of the foreign-body-associated bacteria is postulated to be an important factor. Numerous reports have demonstrated that metabolically less active bacteria are tolerant to the killing effects of most antibiotics (3,4,(9)(10)(11). One paper suggested that there was decreased metabolic activity of Klebsiella pneumoniae after prolonged incubation on polycarbonate filter membranes (28).…”
mentioning
confidence: 99%